2014
DOI: 10.1007/s10006-014-0473-2
|View full text |Cite
|
Sign up to set email alerts
|

A simplified approach to the minimally invasive antral membrane elevation technique utilizing a viscoelastic medium for hydraulic sinus floor elevation

Abstract: This simplified technique may make the minimally invasive antral membrane elevation technique more accessible to implant surgeons as it eliminates the need for purchase of specialized equipment and aids in further decrease of intra-operative time accomplished with the original technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 21 publications
(24 reference statements)
0
6
0
Order By: Relevance
“…The present study supports the use of a minimally invasive implant device in a non-submerged technique for maxillary sinus augmentation with simultaneous implant placement. This hydraulic technique for sinus augmentation was extensively described in the literature [38][39][40][41][42][43][44][45][46][47]. Chen et al reported in 2009 a ten-year follow-up.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study supports the use of a minimally invasive implant device in a non-submerged technique for maxillary sinus augmentation with simultaneous implant placement. This hydraulic technique for sinus augmentation was extensively described in the literature [38][39][40][41][42][43][44][45][46][47]. Chen et al reported in 2009 a ten-year follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al reported in 2009 a ten-year follow-up. The operators were able to predictably elevate the Schneiderian membrane, introduce bone graft, and place implants [38][39][40][41][42][43][44][45][46][47].…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with other studies. The pneumatization of the maxiallary sinus stabilizes after the initial three years shrinkage (Kotsakis & Mazor 2015)…”
Section: Discussionmentioning
confidence: 99%
“…For example, the balloon technique is an indirect sinus elevation method [34], performed with application of a balloon via a transcrestal approach that elevates the sinus membrane while the balloon inlates. Another method used does not involve a bone graft.…”
Section: Paranasal Sinuses 48mentioning
confidence: 99%